On liberty - "Mill, John Stuart" (London, 2010)
In one of the most influential philosophical works ever writer, John Stuart Mill explores the risks and responsibilities of liberty. Examining the tyranny that can come both from government and from the herd-like opinion of the majority, Mill proposes a freedom to think, unite, and pursue our pleasures as the most important freedoms, as long as we cause no harm to others. GREAT IDEAS. Throughout history, some books have changed the world. They have transformed the way we see ourselves - and each other. They have inspired debate, dissent, war and revolution. They have enlightened, outraged, provoked and comforted. They have enriched lives - and destroyed them. Now Penguin brings you the works of the great thinkers, pioneers, radicals and visionaries whose ideas shook civilization and helped make us who we are.
Keywords: Liberty